Analysis of International Tests (PISA, TIMSS and PIRLS) in the Context of Neoliberal Education Policies and Equality of Opportunity in Education - Celebi, Nurhayat; Guner, Halim; Kaya, Gulsah Tasci; Korumaz, Mithat (KARABUK UNIV, 2014)
Until today most of the study on the relationship between Economics and Education has been discussed. As a result education has been perceived as a tool which serves for economic policies. It is commonly accepted that the unequal system designed by capital policies has been reproduced via education. By the way, setting standards for education and assimilate to educational systems to each other all around the world on the purpose of marketing economies is thought to be a fundamental aim of neo-liberal policies. Worldwide tests such as PISA, TIMMS and PIRLS which have effect to reveal the need for reforms for countries, are the keys of setting similar educational systems in different countries or societies. The final reason of revealing these needs is more competitive educational systems for more competitive market policies. Unequal order both in education and economic policies might be deeper according to socio-economic classes. However these worldwide tests' results suggests countries to have more equal educational systems, they cause more deeper unfair application in educational systems which aims to keep up with more successful ones. The aim of this research is to discuss these theoretical problems in the light of the literature. It is highly expected to contribute changing process in Turkey.
Keywords: International Tests; Unequalness in Education; Neo-liberal Policies; PISA; TIMSS; PIRLS; Arts & Humanities - Other Topics